2014
DOI: 10.3109/14767058.2014.944155
|View full text |Cite
|
Sign up to set email alerts
|

Can we identify risk factors during pregnancy for thrombo-embolic events during the puerperium and later in life?

Abstract: Maternal age, grandmultiparity, pregnancy-related hypertension, CD, obesity, stillbirth and peripartum hysterectomy are independent risk factors for the development of VTE. CD and blood transfusion were predictive of early versus late VTE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
2
5
0
Order By: Relevance
“…While pregnancy-associated VTE is well characterized, few studies have identified maternal age as a risk factor for VTE in pregnancy. [22][23][24] In the present study AMA was associated with a sixfold increased risk of VTE. The mechanism for this is not well understood but we speculate that the combined effect of pregnancy-induced hypercoagulability and age-associated endothelial damage may play a role in this observation.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…While pregnancy-associated VTE is well characterized, few studies have identified maternal age as a risk factor for VTE in pregnancy. [22][23][24] In the present study AMA was associated with a sixfold increased risk of VTE. The mechanism for this is not well understood but we speculate that the combined effect of pregnancy-induced hypercoagulability and age-associated endothelial damage may play a role in this observation.…”
Section: Discussionsupporting
confidence: 58%
“…While pregnancy‐associated VTE is well characterized, few studies have identified maternal age as a risk factor for VTE in pregnancy . In the present study AMA was associated with a sixfold increased risk of VTE.…”
Section: Discussionsupporting
confidence: 47%
“…The study concluded that maternal age, obesity, pregnancy-related hypertension, grand multiparity, cesarean delivery, stillbirth and peripartum hysterectomy are independent risk factors responsible for the development of VTE. [ 18 ] A study by Kloviate et al ., compared obese people with normal weighted people to assess the risk of DVT. The study observed that 10-year risk of DVT was high in 35% of the obese people and was only 18% in normal-weight individuals.…”
Section: Discussionmentioning
confidence: 99%
“…A history of stillbirth is associated with a 50% increased odds of composite CVD (OR 1.49 [95% ICI: 1.08–2.06]), 14 a 20% increased probability of CHD (HR 1.18 [95% CI: 1.03–1.37]) 40 and 25% increased probability of CKD (aHR 1.26 [95% CI: 1.09–1.45]) 29 . It confers an almost two‐fold higher probability of future dementia (HR 1.86 [95% CI: 1.28–2.71]) 41 and a 2.5‐fold probability of future VTE (HR 2.56 [95% CI: 1.09–6.05]) 42 . Whether there is a variation in risk depending on the underlying cause has not been explored.…”
Section: Stillbirthmentioning
confidence: 99%